THE EFFECT OF GALLERY WALK STRATEGY ON STUDENTS' WRITING ABILITY IN DESCRIPTIVE PARAGRAPH OF TENTH GRADE AT SMK SWASTA PALAPA BINJAI - Conny Conny; Rudangta Br. Ginting (Jurnal Scientia, 2021)
The objective of this study is to find out the effect of effect of gallery walk strategy on students' writing ability in descriptive paragraph. This study applied quasi experimental research. This study was conducted of the tenth grade students at SMK Swasta Palapa Binjai as the population of the study. The sample was selected by using random sampling, with 50 students as the sample of this study. the writer used clas X-AP which consist of 25 students as the experimental class and X-TSM which consist of 25 students as controlled class.. The data collected from this study were analyzed using t-test formula. The result from calculating the data was t-observation (to = 7,73) and t-table (tt = 1.67). Based on the statistical calculation, it showed that to is higher than tt in significant level 5%. Therefore the alternative hypothesis (Ha) is accepted and the null hypothesis (Ho) is rejected. It means that there was an effect of Gallery Walk Strategy on Students’ Writing Ability in Descriptive Paragraph of Tenth Grade at SMK Swasta Palapa Binjai.